(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to investigate how linguistic courtesy techniques are developed in the fields of Science, Technology, Engineering, and Mathematics (STEM) as well as in the social sciences and humanities at universities in Iraq. This study is grounded in the politeness theory by Brown and Levinson alongside Goffman’s concept of face, this study used a mixed-method design with two data collection instruments. Questionnaires were distributed to 200 students and 20 faculty members, and semi-structured interviews were conducted with 10 faculty members. The findings show that faculty from the humanities tend to employ a more indirect and inclusive language, while STEM/science instructors prefer clear and direct language. The academic discourse and culture of the Iraqi population play a major role in Iraqi education. The paper concludes with practical suggestions for context-sensitive academic.